2022
DOI: 10.3390/en15051905
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of the Hydrodynamic Performance of Slanted Axial-Flow Urban Drainage Pumps at Shut-Off Condition

Abstract: Increasing extreme rainfall events caused by global climate change have had a significant impact on urban drainage systems. As a critical component of a pumping station, a large-scale slanted axial-flow pump (SAFP) featuring high specific speed plays a critical role in mitigating urban flooding and waterlogging. In this study, to reveal the transient characteristics of a SAFP at shut-off conditions, a computational fluid dynamics (CFD) based approach with dynamic mesh was proposed. Multiple shut-off conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Leonow and Mönnigmann (2013) found that this method is only sufficient when single-speed pumps or a narrow range of pump speeds can be assumed for prolonged periods of time. This is largely due to the fact that the transitional stages in pumping (start-up, speed change, and shut-off) lead to instability in pumping operations and complex, two-phase flow (Zhang et al, 2021;Tong et al, 2022) largely due to lags and delays in the pump motor and stator current draw…”
Section: Flowmeter Measures Of Flow Rate [Gpm]mentioning
confidence: 99%
“…Leonow and Mönnigmann (2013) found that this method is only sufficient when single-speed pumps or a narrow range of pump speeds can be assumed for prolonged periods of time. This is largely due to the fact that the transitional stages in pumping (start-up, speed change, and shut-off) lead to instability in pumping operations and complex, two-phase flow (Zhang et al, 2021;Tong et al, 2022) largely due to lags and delays in the pump motor and stator current draw…”
Section: Flowmeter Measures Of Flow Rate [Gpm]mentioning
confidence: 99%
“…In the oil and gas industry, previous research regarding water-hammer effects mainly focused on the sand production issue in wellbores. The emergency shut-in of injection wells may induce large pressure pulses that can cause wellbore integrity problems, such as sand-face failure and sand production [27,28]. This issue has drawn more concerns in offshore wells, where a higher safety criterion is required for platforms and facilities above sea [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [28] studied the hydraulic characteristics of a three-side inlet of vertical shaft inlet channel of a horizontal pumping station based on the Navier-Stokes equations and RNG k-ε turbulence model. Tong et al [29] used the CFD method to study the hydrodynamic performance of slanted axial-flow urban drainage pumps under shut-off conditions. Lu et al [30] compared the hydraulic performance of submersible tubular pump devices with motor front and rear arrangements by the CFD method.…”
Section: Introductionmentioning
confidence: 99%